The Interplay Between Language Form and Concept During Language Switching: A Behavioral Investigation - Zhang, Yong; Cao, Ningning; Yue, Chang; Dai, Lina; Wu, Yan Jing (Frontiers in Psychology, 2020)
Language switching involves changes in multiple sub-linguistic levels. Previous studies have not dissociated switches at the level of language form from those of the concept. Here, we examined the independent contributions of the two factors using a novel language-switching paradigm. Chinese-English bilinguals named individually presented pictures in either Chinese or English according to a language cue. Pictures in two consecutive trials were either identical, semantically related, or unrelated. Results showed the classic language switch costs in all three conceptual conditions. Semantic facilitation effects were observed when naming latencies were compared between the repeated, semantically related, and unrelated condition. Critically, the semantic facilitation effects were 1) independent of (i.e., a main effect) and 2) stronger as compared to the language switch costs as explained by the interaction. These findings suggest that, unlike generic code-switching tasks, language control in bilingual speech production involves multiple levels of loci. Implications of the findings were discussed in the Inhibitory Control and other related models.